The Implementation of Omnibus Law in Indonesia Law Making Process on Philosophy Review - Putu Eva Ditayani Antari (Fakultas Syariah, 2022)
The omnibus law is a method of law-making in Indonesia that began to be applied when the creation of the Job Creation Act was established. The adaptation of this method is controversial because in addition to aiming to simplify Indonesian regulations, it also violates the provisions of the formation of laws regulated in the law. The implementation of this omnibus law is the focus of research studies that lead to discourses based on schools of legal philosophy, especially the Positivism and Legal Realism schools which lead to contradictory conclusions. In order to answer this question, a juridical literature research will be carried out based on an understanding of the various schools of law based on philosophy, using primary legal materials and secondary legal materials. The results of the study conclude that legal positivism requires omnibus law to be stipulated in law as a method of law formation before it is implemented, so that it can provide legitimacy to its position in Indonesian legislation. Meanwhile, legal realism views that the presence of omnibus law is the will of the community and must be responded to in a responsive manner to overcome the excess regulations that occur in Indonesia and tend to overlap.